Analisis Putusan Perkara Penjualan Minuman Beralkohol di Kota Sukabumi - Pratama, Gilang Ali; Juhana, Ujuh (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
The study aims to analyze the judgment of a judge against the perpetrators of the violation of the sale of alcoholic beverages in Sukabumi City due to the abundance of the distribution of alcoholics and violations of the prohibition laws on alcoholic drinks. The method used in the research is the normative jurisprudence of the data used in this research is primary data in the form of court rulings and secondary data contained in legislative regulations, books and journals. The results of the research showed that a quick-check justice system was used to prosecute perpetrators of violations of the sale of alcoholic beverages. The judge takes into account legal certainty, justice, and profit when making a decision, but such a decision cannot have a criminal effect on the offender.